Psikologi Anti-Materialisme - Aftina Nurul Husna (Faculty of Psychology Universitas Gadjah Mada, 2016)
Materialism is a widely used term to identify values or life orientation that stresses the importance of having wealth in life. Approximately 30 years’ worth of studies on materialism have concluded that materialistic orientation, both caused and influenced, unhappiness. Recent studies of materialism begin to test the hypothesis that change/decrease in materialism affects changes/increase in happiness or well - being, raising suggestions to support values contrary to materialism which is healthier for human life. Values opposite to materialism can be counteracted as anti - materialism. In psychology, this concept has not been expl ored, seen from the absence of an empirical study that seeks to know the anti - materialist values. The purpose of writing this article is to inform that anti - materialism may be investigated and developed. This article will describe; (1) the development of m aterialism studies; (2) the theoretical conceptualization of anti-materialism; and (3) the invitation to make anti-materialism the focus of future research